Analisis Kelembagaan Pemerintahan Nagari di Kabupaten Solok Provinsi Sumatera Barat - Desna Aromatica; Heru Nurasa; Ida Widianingsih; Entang Adhy Muhtar (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2018)
Changing of the village government being the Nagari government in West Sumatra has occurred since 2001.  Its aim is in order to implement a government according to the society characteristic West Sumatra that is the custom society.  The first regency implementing the Nagari government is Solok. During the implementations of Nagari government in Solok Regency has not been right enough. The problems arise such as a poor coordination between Badan Musyawarah Nagari and the Nagari government, the poor public services, the role of society leaders is limited.  An Institution is a value and norm to be a reference for the member to act reaching the aim. That research is the analysis of the Nagari government institution, and the research method is using qualitative. The result showing that the Nagari government institution is not built through a value, lifestyle, and norm in the custom society. So, we could say that the Nagari government is the same as the village government, based on the regulation No 5/1975 about the village government. Hence, we require the design of the Nagari government institution to build the Nagari government according to the lifestyle and custom society characteristic.